1997
DOI: 10.18388/abp.1997_4450
|View full text |Cite
|
Sign up to set email alerts
|

Changes in ATP level and iron-induced ultra-weak photon emission in bull spermatozoa, caused by membrane peroxidation during thermal stress.

Abstract: ATP level, cell motility and viability, oxygen uptake, pyruvate kinase activity, and ultra-weak photon emission (UPE) induced by red-ox Fe(2+)-ascorbate cycling system were studied in fresh, in previously equilibrated in a glycerol diluent, and in cryopreserved bull spermatozoa, exposed to thermal stress by incubation of the cells at 44 degrees C. A sharp drop in motility and viability of fresh spermatozoa and even more so, of equilibrated and cryopreserved cells was accompanied by accumulation of ATP. When ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Measurement of ATP level may provide information on the efficiency of metabolic mechanisms that control energy production and consumption in the cell. However, data concerning the relationship between ATP level, sperm motility and fertility are inconsistent (GUMIÑSKA et al 1997;MINELLI et al 1999;TORRES-FLORES et al 2011) and this issue needs further study.…”
mentioning
confidence: 97%
“…Measurement of ATP level may provide information on the efficiency of metabolic mechanisms that control energy production and consumption in the cell. However, data concerning the relationship between ATP level, sperm motility and fertility are inconsistent (GUMIÑSKA et al 1997;MINELLI et al 1999;TORRES-FLORES et al 2011) and this issue needs further study.…”
mentioning
confidence: 97%
“…However, abnormal sperm midpiece organization may be unrelated to mitochondrial energy efficiency. DFX may help to remove iron overload from sperm mitochondria, which has been associated with low ATP generation and alteration of sperm motility as well as with increased ROS generation [ 4 , 54 58 ]. It is of interest to note that in agreement with our observations, Perera et al reported that an increase in sperm DNA damage was recorded upon initiation of iron chelation therapy in β -thalassemic patients with iron overload [ 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…The chemical energy required for sperm motility is supplied by the mitochondria in the form of adenosine triphosphate (ATP). The firefly luciferin-luciferase assay has been used to quantity ATP content in sperm from a wide variety of species, including boar (Aalbers et al, 1985), bull (Guminska et al, 1997) and human (Mendeluk et al, 1997).…”
Section: Discussionmentioning
confidence: 99%